Global, regional, and national burden and projections to 2050 of occupational carcinogen-attributable nasopharyngeal and laryngeal cancer: a comprehensive analysis from the GBD 2021 study - Zhang, Hao; Xue, Rong; Kong, Xinru; Zhao, Manyi; Jin, Zhanguo (Frontiers in Public Health, 2025)
BackgroundOccupational carcinogens contribute to the burden of nasopharyngeal (NPC) and laryngeal cancer (LC), yet their global impact and long-term trends remain insufficiently explored. This study estimates the burden, temporal trends, and future projections of occupational carcinogen-attributable NPC and LC from 1990 to 2050.MethodsUsing data from Global Burden of Disease (GBD) 2021, we analyzed death and disability-adjusted life years (DALYs) across 204 countries and territories. Age-standardized death rate (ASDR), age-standardized DALYs rate, and estimated annual percentage change (EAPC) were used to assess trends. Decomposition analysis quantified the contributions of epidemiological changes, population growth, and aging. Future projections (2022–2050) were estimated using autoregressive integrated moving average (ARIMA) and exponential smoothing (ES) models.ResultsBetween 1990 and 2021, global deaths due to occupational carcinogen-attributable NPC increased by 25.4%, while DALYs rose by 17.0%, despite a 33.3% decline in the age-standardized rate (ASR) of DALYs. For LC, deaths cases increased by 29.4%, and DALYs rose by 22.0%, alongside a 42.9% reduction in ASDR and 42.7% in ASR of DALYs. Sex-specific trends revealed that males bore a disproportionately higher burden, particularly in high-risk occupational sectors. Across socio-demographic index (SDI) regions, the most significant increases in absolute burden were observed in low-middle and middle SDI regions, whereas high SDI regions exhibited the greatest declines in death and DALY rates. Decomposition analysis showed that population growth and aging were the primary drivers of increased burden in low- and middle-income regions, whereas epidemiological improvements helped offset burden in high-income regions. Projections to 2050 suggest that despite further reductions in age-standardized rates, the absolute number of deaths and DALYs will continue rising, particularly in regions experiencing rapid industrialization.ConclusionThe increasing absolute burden despite declining rates underscores the need for sustained occupational health interventions, particularly in low- and middle-income regions. Efforts such as expanding occupational health surveillance systems, tailoring region-specific exposure controls, and improving early-warning prediction tools will be essential to mitigating future occupational cancer risks.